Is That a Rodent in Your Luggage? A Mixed Method Approach to Describe Bushmeat Importation into the United States. (16th May 2013) - Bair‐Brake, H.; Bell, T.; Higgins, A.; Bailey, N.; Duda, M.; Shapiro, S.; Eves, H. E.; Marano, N.; Galland, G.
Summary Bushmeat, defined as meat derived from wild animals, is a potential source of zoonotic pathogens. Bushmeat from restricted animals is illegal to import into the United States under US federal regulations. We reviewed US Centers for Disease Control and Prevention (CDC) port of entry surveillance records from September 2005 through December 2010 and conducted focus group studies to describe trends in and reasons for bushmeat importation into the United States. In total, 543 confiscated bushmeat items were recorded. Half of the confiscated bushmeat items identified were rodents. Africa was the most frequent continent of origin. Seasonality was evident, with bushmeat confiscations peaking in late spring to early summer. Four times more bushmeat was confiscated during an enhanced surveillance period in June 2010 compared with the same period in previous years, suggesting that routine surveillance underestimated the amount of bushmeat detected at US Ports of Entry. Focus groups held in three major US cities revealed that bushmeat importation is a multifaceted issue. Longstanding cultural practices of hunting and eating bushmeat make it difficult for consumers to acknowledge potential health and ecologic risks. Also, US merchants selling African goods, including bushmeat, in their stores have caused confusion among importers as to whether importation is truly illegal. Enhancing routine surveillance for bushmeat and consistent enforcement of penalties at all ports of entry, along with health education aimed at bushmeat importers, might be useful to deter illegal importation.